Developing entrepreneurial mindset for transformational entrepreneurship: The case of Nordic transformative learning circles - Victoria Konovalenko Slettli (Journal of Entrepreneurship, Management and Innovation)
Developing entrepreneurial thinking and mindset has recently been on the agenda of the EU policy makers and is a matter of educators’ concern. Traditional approaches to entrepreneurial education fail to address the ambiguities of the entrepreneurial process. This paper sets out to explore the learning processes that contribute to developing an entrepreneurial mindset for transformational entrepreneurship. Transformational entrepreneurship refers to a capability and an intended action towards creating change in the life of an entrepreneur and organization which contributes to societal changes and is characterized by the emergence of a new qualitative dimension of possibilities (Staffas, 2017). In order to promote transformational entrepreneurship, a particualar adult learning model known as Transformative Learning Circles was elaborated by Nordic Network for Adult Learning with the support of Nordic Council of Ministers. This article is based on the study of the pilot implementation of the TLC model in the context of Nordic countries. The findings reveal that learning processes promoting entrepreneurial mindsets for transformational entrepreneurship occur in three particular phases: 1) framing the praxis; 2) amplifying the frame of reference; and 3) reinterpreting the praxis. The study extends current knowledge about entrepreneurial learning in two ways. First, it links the key factors influencing entrepreneurial learning to concrete learning processes facilitating the development of an entrepreneurial mindset for transformative entrepreneurship. Second, it illustrates how these key factors may be utilized together in one learning model reinforcing the learning and transformative effect.